A case study of Public Administration students’ policy communication readiness via TikTok in Blitar - Sholikhi, Fu'ad (Journal of Language, Literature and Teaching, 2025)
In today's world of transparent budgeting, English proficiency is essential for students pursuing a degree in Public Administration. This study investigates students' perspectives about the efficiency of TikTok as a medium for learning English as a Second or Additional Language (ESL). A total of twelve students enrolled in the Public Administration program at the University of Islam Balitar participated in the study. The study employed a qualitative case approach. Data is collected through in-depth interviews and classroom observations. It is then analyzed thematically. TikTok has been found to be an effective tool for enhancing vocabulary and pronunciation skills related to APBD, as well as for increasing motivation to learn through interactive micro-learning content. However, it should be noted that this approach may also result in distractions and difficulties in distinguishing between educational content and personal opinions without the guidance of a faculty member. According to this study, TikTok has the potential to be a beneficial learning tool for students studying administration, but it must be paired with increasing digital literacy and providing proper direction to avoid any potential adverse effects.